Resource Windfalls and Emerging Market Sovereign Bond Spreads : The Role of Political Institutions - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2010)
We examine the effect that revenue windfalls from international commodity price shocks have on sovereign bond spreads using panel data for 30 emerging market economies during the period 1997-2007. Our main finding is that positive commodity price shocks lead to a significant reduction in the sovereign bond spread in democracies, but to a significant increase in the spread in autocracies. To explain our finding we show that, consistent with the political economy literature on the resource curse, revenue windfalls from international commodity price shocks significantly increased real per capita GDP growth in democracies, while in autocracies GDP per capita growth decreased.